Kekuatan Hukum Memorandum of Understanding Bagi Perlindungan Pekerja Migran Indonesia - Astriyani Irawan; Arman Anwar; Dyah Ridhul Airin Daties (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The governments of Indonesia and Malaysia agreed on a Memorandum of Understanding or MoU on the Placement and Protection of Indonesian Migrant Workers (PMI) in the Domestic Sector in Malaysia. However, three months after the signing, the Government of Malaysia proved to have not carried out the contents of what had been agreed upon in the agreement. Purposes of the Research: Adding knowledge to the author about how the position and legal power of signing a memorandum of understanding or Memorandum of Understanding (MoU) for the protection of migrant workers (PMI) and as input material for academics, government, society, especially PMI candidates and can also be useful for parties who wish conducting research in the same field. Methods of the Research: normative legal research. The nature of the research is descriptive analysis by examining library materials using the Act approach, Concept Approach, and Case Approach. The use of legal material sources consists of primary and secondary legal materials to discuss the formulation of the problem. Results of the Research: The MoU has binding power in providing protection for Indonesian Migrant Workers who are in Malaysia. One of the implications of the MoU is the abolition of the online maid system (SMO) and replaced with a One-channel system (OCS). It is suggested to the Government of Malaysia to respect the provisions agreed in the MoU. Also to the Government of Indonesia to continue monitoring and evaluating the implications of the MoU on the Protection of Indonesian Migrant Workers (PMI) in Malaysia.